Progresses, Challenges, and Prospects of Genome Editing in Soybean (Glycine max) - Xu, Hu; Zhang, Lixiao; Zhang, Kang; Ran, Yidong (Frontiers in Plant Science, 2020)
Soybean is grown worldwide for oil and protein source as food, feed and industrial raw material for biofuel. Steady increase in soybean production in the past century mainly attributes to genetic mediation including hybridization, mutagenesis and transgenesis. However, genetic resource limitation and intricate social issues in use of transgenic technology impede soybean improvement to meet rapid increases in global demand for soybean products. New approaches in genomics and development of site-specific nucleases (SSNs) based genome editing technologies have expanded soybean genetic variations in its germplasm and have potential to make precise modification of genes controlling the important agronomic traits in an elite background. ZFNs, TALENS and CRISPR/Cas9 have been adapted in soybean improvement for targeted deletions, additions, replacements and corrections in the genome. The availability of reference genome assembly and genomic resources increases feasibility in using current genome editing technologies and their new development. This review summarizes the status of genome editing in soybean improvement and future directions in this field.